Multifunctional Solvent Molecule Realizing High-Performance Elastic Polymer Electrolytes for Lithium Metal Batteries - Pimchanok Nipatwarakan; Junlin Song; Yujie Cui; Decai Guo; Yongyi Song; Winadda Wongwiriyapan; Jin Niu; Feng Wang (ACS Applied Materials & Interfaces, 2025)
after 320 cycles at 0.5 C.
Keywords: Advanced Battery Materials and Technologies; Advancements in Battery Materials; Advanced Battery Technologies Research